The lake of dreams [compact disc, unabridged] - Edwards, Kim, 1958- (Penguin Audio, 2011)
The story of a woman's homecoming, a family secret, and the old house that holds the key to the true legacy of a family. At a crossroads in her life, Lucy Jarrett returns home from Japan, only to find herself haunted by her father's unresolved death a decade ago. Old longings stirred up by Keegan Fall, a local glass artist who was once her passionate first love, lead her into the unexpected. Late one night, as she paces the hallways of her family's rambling lakeside house, she discovers, locked in a window seat, a collection of objects that first appear to be useless curiosities. But soon they reveal a deeper and more complex family past. As Lucy discovers and explores the traces of her lineage from an heirloom tapestry and dusty political tracts to a web of allusions depicted in stained glass windows throughout upstate New York, the family story she has always known is shattered. Lucy's quest for the truth reconfigures her family's history, links her to a unique slice of the suffragette movement, and yields dramatic insights that embolden her to live freely.